Analisis Islamic Parenting dalam Penguatan Karakter Prososial Anak: Studi Kasus di RA Tarbiyatun Najah Desa Citapen - Marlina, Dina; Hanifah, Dinda; Riyadi, Hendar; Faatinisa, Esty; Yuniarti, Sani; Fauziah, Shafi Maulida (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to explore Islamic parenting practices in strengthening the prosocial character of early childhood children at RA Tarbiyatun Najah, located in Citapen Village. The background of this study focuses on the significance of Islamic parenting in shaping prosocial character, which is considered an important foundation for children's social and emotional development. The method used in this study is a qualitative approach with a case study design, involving observations and interviews with teachers and parents. The results of the study indicate that the implementation of Islamic parenting in the school environment, through various methods such as role models, habituating prayer, teaching the value of monotheism, and giving praise for good behavior, has proven effective in shaping children's prosocial behavior. The prosocial behavior in question includes actions of sharing, helping, cooperation, and empathy. However, on the other hand, Islamic parenting practices in the family context are still limited to aspects of religious rituals. There are shortcomings in the habituation of morals and direct role models due to limited time and parental knowledge. The implications of this study emphasize the importance of closer collaboration between schools and families. Furthermore, this study also demonstrates the need for mentoring programs for parents to optimally strengthen children's prosocial character. With consistent Islamic parenting, it is hoped that children's prosocial character will develop well, enabling them to grow into individuals with a strong sense of social awareness and the ability to interact effectively within society. This research provides valuable insights for developing more effective parenting styles in the context of early childhood education and encourages increased parental awareness of the importance of their role in educating their children.